(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to evaluate and compare the levels of self-esteem of male and female bodybuilders. Methodology: A quantitative, cross-sectional and descriptive and comparative approach was adopted. The sample comprised 120 bodybuilding practitioners, 60 male and 60 female, with an average age of 25 years in both groups. Rosenberg’s Self-Esteem Scale was used for data collection. The data were treated statistically in the software SPSS 20.0, in a descriptive and inferential way. Results: The general averages obtained were 2,57±0,61 and 2,57±0,78, for the female and male groups, respectively. The practitioners indicated self-esteem classified as average. Comparisons did not indicate any statistically significant difference. Final considerations: The men and women investigated for bodybuilding investigated, with equivalent practice time, have similar self-esteem. Thus, it is possible to assume that the regular practice of physical exercise, in this case, weight training, can contribute to raise the individual’s self-esteem levels.